2013
DOI: 10.4037/ajcc2013283
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Withdrawal Prevention: A Randomized Evaluation of Lorazepam and Ethanol--A Pilot Study

Abstract: Background Alcohol withdrawal syndrome, characterized by a hyperadrenergic state with confusion, agitation and hallucinations, has detrimental effects on patient safety in the context of acute myocardial infarction (MI). Unexpected hospitalization and sudden cessation of alcohol consumption may result in adverse outcomes including in-hospital complications, increased length of stay, and death. Strategies for safe and effective patient management have not been rigorously studied. Purpose We conducted a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…One randomized controlled trial evaluating enteral ethanol for AWS met our inclusion criteria . This single‐center study identified 57 patients admitted to the cardiac intensive care unit (CCU) who were at high risk for withdrawal.…”
Section: Management Of Alcohol Withdrawal Syndromementioning
confidence: 99%
“…One randomized controlled trial evaluating enteral ethanol for AWS met our inclusion criteria . This single‐center study identified 57 patients admitted to the cardiac intensive care unit (CCU) who were at high risk for withdrawal.…”
Section: Management Of Alcohol Withdrawal Syndromementioning
confidence: 99%
“…This practice might halt the progression from mild to severe withdrawal and prevent delirium tremens. 18,20 Use of Serum Biomarkers to Detect an AUD A serum laboratory test that could highlight chronic alcohol use would be helpful, especially when an alcohol history is unobtainable. Laboratory tests such as serum ethanol levels only reveal recent alcohol consumption, not the chronic intake of alcohol that predisposes to withdrawal.…”
Section: Identifying Icu Patients At Risk For Alcohol Withdrawalmentioning
confidence: 99%
“…Bartrug et al [10] reported that 24% developed DT, and of these 11% died and an additional 56% had serious complications, which involved patients with a high risk for acute AWS. Additionally, as a result of AWS or DT complications, costs to both the patient and the health care system are a significant factor in providing safe care for these patients [1]. Joy and Kumar [6] reported that the median LOS for patients with ACS was significantly higher for those with AWS (7 days) and DT (11 days) when compared to nonalcoholics (3 days).…”
mentioning
confidence: 99%
“…In cases of DT coexisting with ACS that is refractory to appropriate high doses of benzodiazepines, early consideration of mechanical ventilation and the administration of phenobarbital, dexmedetomidine or propofol is recommended [11]. Fullwood et al [1] reported that a randomized evaluation of treatment strategies (using lorazepam alone or a combination of ethanol and lorazepam) to prevent complications associated with alcohol withdrawal in acute myocardial infarction is safe and feasible. No specific treatment guidelines exist for the treatment of ACS with coexisting AWS or DT.…”
mentioning
confidence: 99%
See 1 more Smart Citation